Comparative analysis of the anthelmintic efficacy of European heather extracts on Teladorsagia circumcincta and Trichostrongylus colubriformis egg hatching and larval motility - Shepherd Fransesca; Chylinski Caroline; Hutchings Michael R.; Lima Joana; Davidson Ross; Kelly Robert; Macrae Alastair; Salminen Juha-Pekka; Engström Marica T.; Maurer Veronica; Steinshamn Håvard; Fittje Susanne; et al. (BioMed Central Ltd., 2025)
Background
Gastrointestinal nematode (GIN) control is traditionally achieved with the use of anthelmintic drugs, however due to regulations in organic farming and the rise in anthelmintic resistance, alternatives are sought after. A promising alternative is the use of bioactive plant feeding due to the presence of plant secondary metabolites (PSMs) such as proanthocyanidins (PAs). This study focussed on the perennial shrub heather (Ericaceae family), a plant rich in PAs, highly abundant across Europe and with previously demonstrated anthelmintic potential.
Methods
In vitro assays were used to investigate heather’s anthelmintic efficacy against egg hatching and larval motility. Heather samples were collected from five European countries across two seasons, and extracts were tested against two GIN species: Teladorsagia circumcincta and Trichostrongylus colubriformis. Polyphenol group-specific ultraperformance liquid chromatography-tandem mass spectrometry analysis was performed to identify relevant polyphenol subgroups present, including the PA concentration and size and ratio of the subunits. Partial least squares analysis was performed to associate efficacy with variation in PSM composition.
Results
Heather extracts reduced egg hatching of both GIN species in a dose-dependent manner by up to 100%, while three extracts at the highest concentration (10 mg/ml) reduced larval motility to levels that were not significantly different from dead larvae controls. PAs, particularly the procyanidin type, and flavonol derivatives were associated with anthelmintic activity, and the particular subgroup of polyphenols associated with the efficacy was dependent on the GIN species and life stage.
Conclusions
Our results provide in vitro evidence that heather, a widely available plant often managed as a weed in grazing systems, has anthelmintic properties attributed to various groups of PSMs and could contribute to sustainable GIN control in ruminant production systems across Europe.